2019
DOI: 10.3390/molecules24071293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chiral Fungicides Metalaxyl and Metalaxyl-M on the Earthworm Eisenia fetida as Determined by 1H-NMR-Based Untargeted Metabolomics

Abstract: Although metalaxyl and metalaxyl-M are widely used fungicides, very little is known about their subacute and enantiospecific effects on the earthworm metabolome. In this study, Eisenia fetida were exposed to metalaxyl and metalaxyl-M at three concentrations (0.5, 5 and 50 mg/kg) for seven days. 1H nuclear magnetic resonance (1H-NMR)-based untargeted metabolomics showed that metalaxyl and metalaxyl-M exposure disturbed earthworms’ metabolism at all three concentrations. Endogenous metabolites, such as succinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…D was encapsulated into the pores of both host crystalline sponge frameworks 1 (at 50 °C) and 2 (at 25 and 50 °C). 33 , 34 Upon encapsulation into both of the host frameworks, the full structure of D , with atom connectivity consistent with that published previously, 27 , 35 was located and refined with maximum occupancies of 52% in 1.D and 58% in 2.D .…”
Section: Resultssupporting
confidence: 76%
“…D was encapsulated into the pores of both host crystalline sponge frameworks 1 (at 50 °C) and 2 (at 25 and 50 °C). 33 , 34 Upon encapsulation into both of the host frameworks, the full structure of D , with atom connectivity consistent with that published previously, 27 , 35 was located and refined with maximum occupancies of 52% in 1.D and 58% in 2.D .…”
Section: Resultssupporting
confidence: 76%
“…Metalaxyl is the world’s most widely used acetylalanine fungicide, which inhibits the synthesis of ribosomal RNA in mycelium [ 6 ]. Several studies have suggested that metalaxyl is an effective fungicide used for inhibiting Phytophthora nicotianae , Phytophthora infestans and Phytophthora cinnamomi in other plants [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential accumulation of organic pesticides in vineyard soils does not only represent an environmental problem (species might be filtered to ground and/or surface water and affect wildlife in this areas, i.e. invertebrates placed at the lowest levels of food web) (Herrero-Hernández et al, 2016;Schreck et al 2008a;Zhang and Zhou, 2019), but also impacts the enzymatic activity and the microbial community of soil (Marinozzi et al, 2013;Wang et al, 2017). Nowadays, it is accepted that this community affects also to yeast involved in must fermentation and, thus, to the range of volatile organic compounds generated during wine production (Belda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%